2002
DOI: 10.1103/physrevb.65.075420
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen adsorption on an open metal surface:H2/Pd(210)

Abstract: We present self-consistent density-functional calculations of the adsorption of atomic and molecular hydrogen on the ͑210͒ surface of palladium using a plane-wave basis set with optimized ultrasoft pseudopotentials. The layer relaxations of the ͑210͒ surface and the preferred adsorption sites for atomic hydrogen adsorption are determined. Furthermore, we show that on the rather open Pd͑210͒ surface a molecular H 2 adsorption state becomes stabilized by the presence of atomic hydrogen on the surface. This provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
57
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 43 publications
5
57
0
Order By: Relevance
“…Note, that this downshift is not caused by the interaction of the two additional hydrogen atoms with Pd. Atomic hydrogen adsorption hardly changes the LDOS of Pd, as our and previous [21] calculations confirm. It has to be pointed out that the relative intensities of the synthetic valence band spectrum are not well reproduced, which might be attributable to matrix element effects present in the photoemission process.…”
supporting
confidence: 80%
“…Note, that this downshift is not caused by the interaction of the two additional hydrogen atoms with Pd. Atomic hydrogen adsorption hardly changes the LDOS of Pd, as our and previous [21] calculations confirm. It has to be pointed out that the relative intensities of the synthetic valence band spectrum are not well reproduced, which might be attributable to matrix element effects present in the photoemission process.…”
supporting
confidence: 80%
“…The first labels indicate the adsorption energy in a descending order ͑see also Table IV below͒ and the label in parentheses gives the coordination of the S atom at the particular site. Ϫ6.1% Ϫ4.8% Ϫ11.6% Ϫ6.5% ⌬d 5,6 Ϫ2.0% ϩ0.2% ϩ22.8% ϩ18.5% ⌬d 6,7 ϩ3.6% Ϫ8.2% Ϫ6.9% ⌬d 7,8 Ϫ2.7% Ϫ3.1% Ϫ1.7% ⌬d 8,9 ϩ0.0% ϩ6.3% ϩ2.8%…”
Section: Energetics and Relaxations Of Stepped Pd Surfacesmentioning
confidence: 99%
“…7. Relaxations have been considered for the steps on the Pt͑111͒ surface 35,36 and on different Cu surfaces.…”
Section: Energetics and Relaxations Of Stepped Pd Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few exceptions concern Pd (210) [14,15], Pd (311) [16][17][18] and Pd(211) [19]. Despite the general tendency of hydrogen atoms to occupy highly coordinated sites is also preserved on the stepped surfaces, it was shown that the highest energy was not always related to a hydrogen atom being adsorbed on the highest coordinated site [15,19]. In addition, there is a strong need to distinguish between the sites with even the same coordination number as not all of them are equivalent [19].…”
Section: Introductionmentioning
confidence: 99%